ANALISIS PENGARUH PENGHIMPUNAN DANA DAN PEMBIAYAAN TERHADAP FALAH LABA (Studi pada Bank Umum Syariah di Indonesia Periode 2009-2013) - Sany, Ibrahim; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2014)
Bank as intermediary financial in conducting its business activities are classified into two categories, namely conventional banks and banks with Islamic principles. As an investment manager, Islamic banks do fund raising with the principles of customer wadi'ah and mudaraba principle. As an investor, Islamic banks channeling funds through investment activities with the principle of profit-sharing financing, principle of sell-buy, or principle of lease financing.This research investigated the relationship on the principle of profit-sharing financing, principle of sell-buy financing, principle of lease financing, principle of wadiah fund raising and principle of mudaraba fund raising to earning falah of Islamic banks. Total population in this research are registered Islamic bank in Bank Indonesia in 2009-2013, the sample can be used as many as four Islamic banks.The results of hypothesis testing the principle of profit-sharing financing had positive significant effect to earnings falah of Islamic Bank in Indonesia, the principle of sell-buy financing had positive significant effect to earnings falah of Islamic Bank in Indonesia, the principle of lease financing had negative not significant effect to earnings falah of Islamic Bank in Indonesia, the principle wadi'ah fund raising had positive significant effect to earnings falah of Islamic Bank in Indonesia, and the principle of mudaraba fund raising had positive significant effect to earnings falah of Islamic Bank in Indonesia.